LINGUISTIC FEATURES OF AUTHOR’S NEOLOGISMS IN J. K. ROWLING’S NOVEL “HARRY POTTER AND THE PHILOSOPHER’S STONE” - Vasylenko, Oksana; Vozniuk, Liudmyla (Scientific Journal of Polonia University, 2024)
The article deals with the neologisms of J. Rowling who is famous for her creation of Harry Potter series and she is also known for her clever use of language, including the invention of new words and phrases. These neologisms add depth and richness to the wizarding world she has created. There are several ways of creating author’s neologisms, among which syntactic (word-forming derivation), semantic (changes in the meaning of a word, its reinterpretation) and borrowing prevail. It is revealed that J. Rowling formed neologisms using word-forming derivation (suffixing, word formation and abbreviation and semantic derivation but there are no neologisms formed by the morphological type of stem formation in the first two books. The main functions performed by neologisms in the novel are originality, creativity and expressiveness. These neologisms have become integral parts of the Harry Potter universe and have contributed to its enduring popularity. They demonstrate Rowling’s creativity as a writer and her ability to bring her fictional world to life through language.